HIV-1 Drug Resistance and Third-Line Therapy Outcomes in Patients Failing Second-Line Therapy in Zimbabwe. (2nd February 2018) - Chimbetete, Cleophas; Katzenstein, David; Shamu, Tinei; Spoerri, Adrian; Estill, Janne; Egger, Matthias; Keiser, Olivia
Abstract: Objectives: To analyze the patterns and risk factors of HIV drug resistance mutations among patients failing second-line treatment and to describe early treatment responses to recommended third-line antiretroviral therapy (ART) in a national referral HIV clinic in Zimbabwe. Methods: Patients on boosted protease inhibitor (PI) regimens for more than 6 months with treatment failure confirmed by 2 viral load (VL) tests >1000 copies/mL were genotyped, and susceptibility to available antiretroviral drugs was estimated by the Stanford HIVdb program. Risk factors for major PI resistance were assessed by logistic regression. Third-line treatment was provided as Darunavir/r, Raltegravir, or Dolutegravir and Zidovudine, Abacavir Lamivudine, or Tenofovir. Results: Genotypes were performed on 86 patients who had good adherence to treatment. The median duration of first- and second-line ART was 3.8 years (interquartile range [IQR], 2.3–5.1) and 2.6 years (IQR, 1.6–4.9), respectively. The median HIV viral load and CD4 cell count were 65 210 copies/mL (IQR, 8728–208 920 copies/mL) and 201 cells/mm 3 (IQR, 49–333 cells/mm 3 ). Major PI resistance-associated mutations (RAMs) were demonstrated in 44 (51%) non-nucleoside reverse transcriptase inhibitor RAMs in 72 patients (83%) and nucleoside reverse transcriptase inhibitors RAMs in 62 patients (72%). PI resistance was associated with age >24 years ( P = .003) and CD4 cell count <200 cells/mm 3 ( P = .007). In multivariable analysis, only age >24 years was significantly associated (adjusted odds ratio, 4.75; 95% confidence interval, 1.69–13.38; P = .003) with major PI mutations. Third-line DRV/r- and InSTI-based therapy achieved virologic suppression in 29/36 patients (81%) after 6 months. Conclusions: The prevelance of PI mutations was high. Adolescents and young adults had a lower risk of acquiring major PI resistance mutations, possibly due to poor adherence to ART. Third-line treatment with a regimen of Darunavir/r, Raltegravir/Dolutegravir, and optimized nucleoside reverse transcriptase inhibitors was effective.